2015
DOI: 10.3389/fnhum.2015.00061
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the association between functional connectivity of the brain and intellectual performance

Abstract: Measurements of functional connectivity support the hypothesis that the brain is composed of distinct networks with anatomically separated nodes but common functionality. A few studies have suggested that intellectual performance may be associated with greater functional connectivity in the fronto-parietal network and enhanced global efficiency. In this fMRI study, we performed an exploratory analysis of the relationship between the brain's functional connectivity and intelligence scores derived from the Portu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 38 publications
11
59
0
1
Order By: Relevance
“…Speaking to this directly, van den Heuvel and colleagues (2009) found a strong positive relationship between functional network global efficiency and intelligence. This finding has been replicated for different behavioural measures of intelligence (e.g., Pamplona et al, 2015), as well as across imaging techniques (Langer et al, 2011).…”
Section: Functional Network Related To Individual Differences In Intsupporting
confidence: 52%
See 2 more Smart Citations
“…Speaking to this directly, van den Heuvel and colleagues (2009) found a strong positive relationship between functional network global efficiency and intelligence. This finding has been replicated for different behavioural measures of intelligence (e.g., Pamplona et al, 2015), as well as across imaging techniques (Langer et al, 2011).…”
Section: Functional Network Related To Individual Differences In Intsupporting
confidence: 52%
“…As a striking example, in a follow-up study using the same data reported above (Song et al, 2008), Song and colleagues (2009) found that several connections within the default-mode network also correlated with intelligence, suggesting that the existing 'FPNcentric' literature may reflect biased analysis decisions, such as region of interest choice. In line with this, a number of studies have related individual differences in intelligence to resting-state connectivity of the default-mode network and cingulo-opercular network (Pamplona et al, 2015;Santarnecchi et al, 2015;Wang et al, 2011;Yuan et al, 2012). While the CON is often seen as a critical counterpart to the FPN (Seeley et al, 2007), the DMN is considered antagonistic to it .…”
Section: Functional Network Related To Individual Differences In Intmentioning
confidence: 88%
See 1 more Smart Citation
“…The COMT (catechol-o-methyl transferase) polymorphisms relate directly and strongly with IQ scores. The polymorphic gene that leads to a Val166Met mutation in the protein alters the activity of brain-derived neurotrophic factor (BDNF), interfering with cognitive functions (DUNCAN, 2013;OHTANI, NESTOR, BOUIX et al, 2014;PAMPLONA, SANTOS NETO, ROSSET et al, 2015;KOTEN JUNIOR, WOOD, HAGOORT et al, 2009;DEARY, PENKE and JOHNSON, 2010).…”
Section: Thickness Of Cerebral Cortex and Its Correlation With Globalmentioning
confidence: 99%
“…The model of frontoparietal integration (P-FIT model) match the neuroimaging findings, but many functional studies, according to genre and age, will probably modify the intelligence circuits accepted nowadays. Future pharmacologic interventions will be at hand to stimulate or to inhibit specific neurocircuits involved with cognition, open the way to an effective therapy to learning disturbances and neuropsychiatric diseases (GRAY and THOMPSON, 2004;LUDERS, NARR, THONPSOM, 2009;RHEIN, MÜHLE, RICHTER-SCHMIDINGER et al, 2014;PAMPLONA, SANTOS NETO, ROSSET et al, 2015;GLASCHER, TRANEL, PAUL et al, 2009). …”
Section: Genetic Influence In the Global Intelligencementioning
confidence: 99%